Simultaneous Real-Time Detection of Initiator- and Effector-Caspase Activation by Double Fluorescence Resonance Energy Transfer Analysis - Hiroshi Kawai; Takuo Suzuki; Tetsu Kobayashi; Haruna Sakurai; Hisayuki Ohata; Kazuo Honda; Kazutaka Momose; Iyuki Namekata; Hikaru Tanaka; Koki Shigenobu; Ryu Nakamura; Takao Hayakawa; et al. (Elsevier, 2005)
Fluorescence resonance energy transfer (FRET) with green fluorescent protein (GFP) variants has become widely used for biochemical research. In order to expand the choice of fluorescent range in FRET analysis, we designed various color versions of the FRET-based probes for caspase activity, in which the substrate sequence of the caspase was sandwiched by donor and acceptor fluorescent proteins, and studied the potential of these color versions as fluorescent indicators. Six color versions were constructed by a combination of cyan fluorescent protein (CFP), GFP, yellow fluorescent protein (YFP), and DsRed. Real-time monitoring in single cells revealed that all probes could detect caspase activation during tumor necrosis factor (TNF)-α-induced cell death as a fluorescent change. GFP-DsRed and YFP-DsRed were as sensitive as CFP-YFP, and CFP-DsRed also showed a large fluorescent change. By using two probes, CFP-DsRed and YFP-DsRed, we carried out simultaneous multi-FRET analysis and revealed that the initiator- and effector-caspases were activated almost simultaneously in TNF-α-induced cell death. These findings may give experimental bases for the development of novel techniques to analyze multi-events simultaneously in single cells by using FRET probes in combination. Keywords:: fluorescence resonance energy transfer, green fluorescent protein, tumor necrosis factor-α, cell death, caspase